Analisis Kemampuan Literasi Sains dalam Pembelajaran IPAS pada Siswa Kelas IV MI Gedanganak Ungaran Timur - Ismawati, Farihah; Winarti, Puji; Puspitasari, Nimas (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2024)
This research is motivated by the development of the 5.0 revolution era which requires 21st century abilities that must be possessed by all fields, one of which is the field of education. One of the keys to success in facing the challenges of the 21st century is science literacy. The purpose of this study is to describe the science literacy skills of grade IV B MI Gedanganak students in IPAS learning. The type of research used is qualitative research. This research using triangulation techniques. Data were collected through performance tests, observations, and interviews. The results of the study found that the average score of science literacy skills of grade IV B students seen from the content aspect could be categorized as “medium”, the science process aspect is categorized as “low”, the context aspect of science is include in the “high” category, and the attitude aspect can be categorized as “very high”. So learning that is more student-centered is expected to can improve students’ science literacy skills in IPAS learning at school.Keywords: science literacy skills, IPAS learning